The Architecture of Transhumance: An Ethnographic Study of Animal Enclosures in a Pastoral Community in Iran. (2nd July 2016) - Izadpanah, Farzin
Abstract : Maymand is usually referred to as a troglodytic village in Iran, although over the years its transhumant community migrates seasonally across a natural landscape, settling in three special types of habitat: the troglodytic village, ābādihā (gardens) and āqolhā (folds, i.e. enclosures for domestic animals, especially sheep). This paper aims to explore the vernacular architecture of folds as a physical embodiment of the local people's pastoral lifestyle, emphasizing their calendar and social structure, and describing their architectural spaces and settlement patterns from an ethnographic perspective. The author studies folds using an unstructured approach involving participant observation and informal interview over 13 years of investigation. The results provide an insight into the architecture of such folds and reflect the author's effort to understand its meaning in its cultural context.